Classroom engagement in Chinese private colleges: The role of teacher-student interactions and peer relationships - Zhiuan Yang; Connie Shin @ Connie Cassy Ompok; Sabariah Bte Sharif (Conscientia Beam, 2025)
Private higher education in China has emerged as a significant platform for the growth and advancement of higher education, serving as a primary catalyst for reform over more than four decades of transformation. This study focused on undergraduate students from Qingdao Hengxing College located in the eastern coastline region of China to examine the relationships among teacher-student interactions, peer relationships and classroom participation. The researcher employed a survey method, analyzing 534 valid questionnaire responses adopting a positivist paradigm and a quantitative research design. Descriptive statistics, simple linear regression and multiple regression analyses were used to interpret the data. The sample was fairly balanced in terms of gender and academic year. 48.5% were male and 51.5% were female with 22.4%, first-year, 27.5% second-year, 27.9% third year and 22% fourth year students. Results indicated a significant and positive relationship between classroom engagement and both teacher-student interactions (β=0.566 and p<0.001) and peer connections (β=0.550 and p<0.001). These factors explained 40.3% of the variance in classroom engagement. These findings highlight the vital importance of teacher-student interactions and peer relationships in promoting classroom engagement, offering valuable insights for teachers and policymakers in private higher education.